2015
DOI: 10.1039/c5ra12319d
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the surface properties of cerium oxide nanoabrasives through morphology control for glass CMP

Abstract: Nanosized cerium oxide (CeO 2 ) particles possessing different morphologies like nanorods, nanocubes and nanospheres have been successfully synthesized by a simple one step, surfactant free, precipitation technique and by hydrothermal methods. The diverse morphology motifs were further utilized for the planarization of silicate glass with an initial surface roughness of $40 nm and we observed a strong morphology dependence of the abrasive in glass polishing. Polishing efficiency of the nanoabrasives in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
(106 reference statements)
2
13
1
Order By: Relevance
“…19 Sreeremya et al observed a strong morphology dependence of ceria nano-abrasives in glass polishing and the ceria nanostructure with a mixed morphology of rods and cubes exhibited the highest material removal rate and the best surface nish compared to nano-cube and nanosphere. 20 Peng et al carried out contrast experiments using ceria abrasive with micro and nano particle sizes in glass polishing and found that the material was removed by chemical reaction for ceria nanoparticles, while chemical reaction and mechanical abrasion simultaneously took place for ceria particles with sizes at scale of micrometers. 21 In addition to size and morphology of the particle, the polishing performance of ceria abrasive is also affected by the heat treatment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…19 Sreeremya et al observed a strong morphology dependence of ceria nano-abrasives in glass polishing and the ceria nanostructure with a mixed morphology of rods and cubes exhibited the highest material removal rate and the best surface nish compared to nano-cube and nanosphere. 20 Peng et al carried out contrast experiments using ceria abrasive with micro and nano particle sizes in glass polishing and found that the material was removed by chemical reaction for ceria nanoparticles, while chemical reaction and mechanical abrasion simultaneously took place for ceria particles with sizes at scale of micrometers. 21 In addition to size and morphology of the particle, the polishing performance of ceria abrasive is also affected by the heat treatment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…17 Sreeremya et al revealed that the material removal and the nal surface quality were affected mostly by the morphology of the ceria-based abrasives and that the quality of the polished surface could be improved by improving the dispersion of the abrasives. 18 Furthermore, the interaction between the abrasives and the polished surface could be changed by modifying the surface charge of the abrasives and the wafer to inuence the material removal during the CMP process. 19,20 Lagudu et al studied the inuence of the ionic strength on material removal during the CMP of amorphous SiC lm using silica slurries and suggested that the electrostatic repulsion between the silica abrasive and the SiC lm was reduced by the addition of an ionic compound, thereby increasing the material removal.…”
Section: Introductionmentioning
confidence: 99%
“…33 CeO 2 nanoparticles with a mixed morphology of rods and cubes exhibited a better surface finish and the highest material removal rate (MRR) in glass polishing compared with nanocubes and nanospheres. 34 CeO 2 nanooctahedra with {111} facets had a higher MRR for singlecrystal silicon than nanospheres because the abrasion mechanism of the silicon substrate polished by the nanooctahedra with sharp edges and corners was microploughing wear, while that polished by nanospheres was microscale abrasive wear. 35 particles, hierarchical nanospheres of CeO 2 exhibited a superior removal rate and scratch suppression ability in chemical−mechanical polishing (CMP) of a SiO 2 wafer due to their physical softness and high chemical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In glass polishing, nanosized ceria particles mainly achieved material removal through a chemical reaction, while microsized ceria abrasive underwent both a chemical reaction and mechanical friction . CeO 2 nanoparticles with a mixed morphology of rods and cubes exhibited a better surface finish and the highest material removal rate (MRR) in glass polishing compared with nanocubes and nanospheres . CeO 2 nano-octahedra with {111} facets had a higher MRR for single-crystal silicon than nanospheres because the abrasion mechanism of the silicon substrate polished by the nano-octahedra with sharp edges and corners was microploughing wear, while that polished by nanospheres was microscale abrasive wear .…”
Section: Introductionmentioning
confidence: 99%